Pengaruh Brand Image dan Instagram Marketing terhadap Keputusan Pembelian Lazatto Serang - Muhammad Ibnu Bastian; Dedek Kumara (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the effect of brand image and social media on purchasing decisions at Lazatto in Serang City. A quantitative approach with a descriptive and correlational design was employed using a survey method involving 100 respondents selected through accidental sampling. The data were analyzed using simple and multiple linear regression techniques. The results indicate that brand image and social media partially have a positive and significant effect on purchasing decisions. Social media demonstrates a more dominant influence compared to brand image. Simultaneously, both variables significantly affect purchasing decisions with a contribution of 22.8%, while the remaining variance is explained by other factors outside the research model. These findings suggest that strengthening brand image and optimizing digital marketing strategies through social media are essential factors in enhancing consumer purchasing decisions.